Directives Function on the UP Movie - Ni Kadek Yuni Ernayanti; I Dewa Ayu Devi Maharani Santika; Ni Wayan Suastini (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
Abstract Speech act is the part of people utterances. In order to make the hearer to do the what the speaker wants, directives type of ilocutionary act can be used to this situation. This study used the theory proposed by Yule (1996) about the types of illocutionary act in ordered to answer the first problem. Meanwhile to answer the second problem this study used the theory meaning that proposed by Leech (1981) and the theory proposed by Halliday (1989) about the context of situation. This study were used the descriptive qualitative method. There are 16 directives data that were analyzed in this study. According to the analysis there are 13(18,25%) in the function of commanding, 1(6,25%) data in the function of orders, 1(6.25%) data in the function of requests and 1(6,25%) in the function of suggestion. The result of this study showed that the function of command became the most dominant expression that used by the character’s utterance on the UP movie. Besides that there are four types of meaning that found on the character’s utterance which conduct of the directives types of illocutionary act on the UP movie. Those data are included 10 (62,5%) data of conceptual meaning, 4(25%) data of connotative meaning, 1(6,25%) data of social meaning and 1(6,25%) data of thematic meaning. Key words: Illocutionary act, Implied Meaning, UP Movie